The effect of extracorporeal shock wave therapy in coccydynia: a systematic review and meta-analysis. Issue 6 (5th November 2022) - Nikouei, Farshad; Shakeri, Mohammadreza; Ghandhari, Hasan; Motalebi, Mohsen; Ameri, Ebrahim
Abstract : Background: Extracorporeal shock wave therapy (ESWT) has been used in the treatment of coccydynia. However, it has not yet been validated due to the dispersion of studies, the low number of patients, and the use of different measuring instruments. This meta-analysis was performed with the aim of collecting homogeneous studies to achieve a reliable result. Methods: The authors searched electronic databases including Google Scholar, Scopus, ScienceDirect, ISI Web of Science, Embase, and PubMed to find studies in which the effect of ESWT on coccydynia using visual analog scale (VAS) scores was evaluated starting in January 1990 through August 2021. All search procedures were performed by two authors. Results: The mean pain changes of 81 patients from four studies in 1 mo, 2 to 4 mo, and 6 to 12 mo after using ESWT were analyzed. Overall mean change of VAS score in 1 mo, 2 to 4 mo, and 6 to 12 mo after applying ESWT was -42.41 (I 2 =86.96%, 95% confidence interval [CI] of −56.88, −27.94, P =0.001), −41.01 (I 2 =0.0%, 95% CI of −46.98, −35.04, P =0.001) and −50.13 (I 2 =82.41%, 95% CI of −67.33; −32.94, P =0.001), respectively. Conclusions: The authors showed that ESWT lessened pain in patients with coccydynia. This effect did not diminish during a year; instead, it further reduced pain in patients. However, more research is needed to verify the results. Level of Evidence: Level I.